Praktyki dokumentowania i wykorzystania dziedzictwa kulturowego Śląska Cieszyńskiego od początku XIX wieku do wybuchu II wojny światowej - Studnicki, Grzegorz (Studia Etnologiczne i Antropologiczne, 2020)
This article is devoted to an interest in local folk culture, regional heritage, and the past of Cieszyn Silesia, as well as to methods extending back through the 19th century for the documentation, popularization, and protection of the unique cultural knowledge of the region. Attention is primarily given to the activities of the Cieszyn Silesians themselves. The author examines multiple sources, including local periodicals, for elements of local culture (folklore, dialects, traditional outfits, customs). He tries to capture how the phenomena of cultural heritage is defined both regionally and nationally, and also how it can be used as a resource in tourism and in broadly-understood identity policy.